A B-lymphocyte binding peptide from BNRF1 induced antibodies inhibiting EBV-invasion of B-lymphocytes (2005)
Epstein–Barr virus (EBV) infects human target cells mainly through gp350/220-CD21 and gp42-MHCII interactions; however, it has been shown that these interactions are dispensable for EBV-invasion of susceptible cells, suggesting that other viral proteins are involved in this process. It is probable that tegument BNRF1/p140 protein is involved in EBV-invasion of target cells, since anti-p140 antibodies inhibit EBV-infection of B-lymphocytes and there is evidence that part of the protein is located on virus surface. Sixty-six peptides, covering the entire BNRF1/p140 sequence, were synthesised and tested in lymphoblastoid cell line binding assays. Peptides 11465 and 11521 bound with high affinity to Raji, Ramos and P3HR-1 cells but not to erythrocytes, showing cell-binding behaviour similar to EBV. These two peptides induced antibodies recognising live EBV-infected cells. Interestingly, peptide-11521 (YVLQNAHQIACHFHSNGTDA) or antibodies induced by this peptide inhibited EBV-binding to B-lymphocytes, suggesting that this p140-region could be involved in EBV and B-lymphocyte interaction.